Hedonism in Contemporary Society: An Analysis of Social Behavior and Its Relevance to the Story of the Thamud People in the Qur'an - Yasirotul khujjati ya Ramadhina; Amir Mahmud; Miftara Ainul Mufid; Ahmad Zainuddin (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2026)
The phenomenon of hedonism in contemporary society continues to grow alongside the currents of globalization, modernization, and the advancement of social media. A lifestyle oriented toward pleasure, luxury, and material satisfaction has influenced social behavior and given rise to various moral problems, such as consumerism, individualism, and the culture of flexing. This study aims to analyze the forms of hedonistic behavior in contemporary society and their relevance to the story of the Thamud people in the Qur’an. The research method used is qualitative research with a thematic interpretation (maudhu’i) approach to Qur’anic verses related to the Thamud people. Data were collected through library research by examining tafsir literature, scientific journals, and sources related to modern social behavior. The results of the study show that the behavior of the Thamud people bears similarities to today’s hedonistic phenomenon, namely excessive lifestyles, arrogance toward the blessings they possessed, and negligence toward spiritual and moral values. The Qur’an presents the story of the Thamud people as a lesson for humanity not to become trapped in a lifestyle that merely pursues worldly pleasures. This study emphasizes that a balanced, modest way of life oriented toward divine values is the solution offered by the Qur’an in addressing the development of hedonism in the contemporary era.